Transfer of Meropenem in the ex Vivo Human Placenta perfusion Model - Roger E. Bawdon; Michael Hnat (Hindawi Limited, 2005)
Objectives. To determine maternal-fetal transplacental passage of meropenem in the ex vivo human perfusion model.